Blended Learning: Kombinasi Belajar Untuk Anak Usia Dini di Tengah Pandemi - Eva Eriani; Reni Amiliya (STAI Auliaurrasyidin Tembilahan, 2020)
Covid 19 pandemic hitting people arround world caused many changes in various aspects of life which one of them is education field. Government, teachers, families, and even students are required to be able to adapt to the situation. Breaking down the corona virus transmission, the government got deal with the rules of working and studying from home. Concerning the previous session of learning classically conducted, it seemed to be agreed that the rests are designed to be accessed online – which combination (offlne and online) was so called by blanded learning. That’s why the researcher put a high interest on whether it can effectively be applied at pandemic especially for Early Childhood Education. Data was collected through the questionnaires which are onlinely filled out by 30 teachers of 5 kindergartens who carried out blended learning. Data were then analyzed by using a trial scale, percentage formula and SPSS, 16 version. The results showed the effectiveness of the application of blended learning for early childhood when the pandemic was in the good category.